Individual, Household, and Community Drivers of Dengue Virus Infection Risk in Kamphaeng Phet Province, Thailand - Gabriel Ribeiro dos Santos; Darunee Buddhari; Sopon Iamsirithaworn; Direk Khampaen; Alongkot Ponlawat; Thanyalak Fansiri; Aaron Farmer; Stefan Fernandez; Stephen Thomas; Isabel Rodriguez Barraquer; Anon Srikiatkhachorn; Angkana T Huang; et al. (My University, 2022)
Abstract Background Dengue virus (DENV) often circulates endemically. In such settings with high levels of transmission, it remains unclear whether there are risk factors that alter individual infection risk. Methods We tested blood taken from individuals living in multigenerational households in Kamphaeng Phet province, Thailand for DENV antibodies (N = 2364, mean age 31 years). Seropositivity ranged from 45.4% among those 1–5 years old to 99.5% for those >30 years. Using spatially explicit catalytic models, we estimated that 11.8% of the susceptible population gets infected annually. Results We found that 37.5% of the variance in seropositivity was explained by unmeasured household-level effects with only 4.2% explained by spatial differences between households. The serostatus of individuals from the same household remained significantly correlated even when separated by up to 15 years in age. Conclusions These findings show that despite highly endemic transmission, persistent differences in infection risk exist across households, the reasons for which remain unclear.
Keywords: Serostatus; Risk of infection; Mosquito-borne diseases and control